A Novel Gene Controls a New Structure: PiggyBac Transposable Element-Derived 1, Unique to Mammals, Controls Mammal-Specific Neuronal Paraspeckles. (23rd August 2022) - Raskó, Tamás; Pande, Amit; Radscheit, Kathrin; Zink, Annika; Singh, Manvendra; Sommer, Christian; Wachtl, Gerda; Kolacsek, Orsolya; Inak, Gizem; Szvetnik, Attila; Petrakis, Spyros; Bunse, Mario; et al.
Abstract: Although new genes can arrive from modes other than duplication, few examples are well characterized. Given high expression in some human brain subregions and a putative link to psychological disorders [e.g., schizophrenia (SCZ)], suggestive of brain functionality, here we characterize piggyBac transposable element-derived 1 ( PGBD1 ). PGBD1 is nonmonotreme mammal-specific and under purifying selection, consistent with functionality. The gene body of human PGBD1 retains much of the original DNA transposon but has additionally captured SCAN and KRAB domains. Despite gene body retention, PGBD1 has lost transposition abilities, thus transposase functionality is absent. PGBD1 no longer recognizes piggyBac transposon-like inverted repeats, nonetheless PGBD1 has DNA binding activity. Genome scale analysis identifies enrichment of binding sites in and around genes involved in neuronal development, with association with both histone activating and repressing marks. We focus on one of the repressed genes, the long noncoding RNA NEAT1, also dysregulated in SCZ, the core structural RNA of paraspeckles. DNA binding assays confirm specific binding of PGBD1 both in the NEAT1 promoter and in the gene body. Depletion of PGBD1 in neuronal progenitor cells (NPCs) results in increased NEAT1/paraspeckles and differentiation. We conclude that PGBD1 has evolved core regulatory functionality for the maintenance of NPCs. As paraspeckles are a mammal-specific structure, the results presented here show a rare example of the evolution of a novel gene coupled to the evolution of a contemporaneous new structure.